Pengaruh Pelatihan Air Splint terhadap Keterampilan Penanganan Fraktur Ekstremitas Atas dan Bawah di Kusuma Nursing Care-Emergency - Suparmanto, Gatot; Agustin, Wahyu Rima; Utami, Sesa Anindya Nur (Viva Medika, 2023)
The use of Air Splint requires proper skills so that the severity of the wound does not increase and reduce pain and is used as a support for the injured body part. To get this competency, training is needed. This study aims to determine the effect of Air Splint Training on Upper and Lower Extremity Fracture Handling Skills. A quasi-experimental study design without control on 36 members of KNC Emergency, the observed variables are: training in the use of Air Splints in handling upper and lower extremity fractures and use skills in upper and lower extremity fractures. Data analysis used Wilcoxon test. Before being given training, most of them had skills at a moderate level, namely 21 people (58.3%), while those with a high skill level were 5 (13.9%) and 10 people (27.8%) had low skills). After being given training, most of them had a medium skill level, namely 17 people (47.2%), while those with a high skill level were 16 people (44.4%) and those with low skills were 3 (8.3%). There is a difference in the posttest skill level of KNC Emergency members after being given an intervention with p value 0.000 <0.05.